Towards SMV Model Checking of Signal (multi-clocked) Specifications - Peralta, Julio; Gautier, Thierry (Electronic Communications of the EASST, 2009)
Signal is a high-level data-flow specification language that equally allows multi-clocked descriptions as well as single-clocked ones. It has a formal semantics and is supported by several formal tools for simulation and static validation. This generality renders it useful for various specification, simulation, and verification tasks in embedded system design. SMV, in turn, is a language and model checker where synchronous models are single-clocked by definition. Roughly, we use standard techniques to describe clocks by Boolean variables, with the advantage that the number of such variables is kept to a minimum through a static analysis provided by the Signal compiler. In particular, we propose a translation from possibly multi-clocked Signal specifications into SMV specifications for their corresponding verification by model checking.